A Response to Tyson E. Lewis's "A Marxist Education of the Encounter". Issue 4 (2nd October 2019) - Cree, Dylan
Abstract : This response essay contends that Tyson E. Lewis's concept of the seminar as a revolutionary mechanism within the university is based on misunderstandings of Althusser's theory of ideology and class struggle. Lewis formulates interpellation as Althusser's "fundamental educational problematic." To counter, this response clarifies how Althusser analyzes ISAs (with the operations of education as one of the diverse kinds of ISA). Further, it examines interpellation—the ongoing constitution of subjects—as a formation that is precedent to specific engagements in and across all apparatuses. We cannot readily reject, dissolve, or counter interpellation. Rather, interpellation ensnares individuals such that their potential relief from how they are constituted likely leads to another form of constitution—that is, interpellation. In opposition to Lewis, regarding the liberative gains to individuals through the seminar, this response proposes that, while navigating Althusser's problematic, we keep in mind that revolution is not external to apparatuses or productive processes.